Identifying Communication Flow in the Development of Apartment Project X to Enhance Time Performance - Aditama, Satya; Riantini, Leni Sagita (Dinasti International Journal of Digital Business Management, 2024)
This research aims to develop a risk-based communication flow in apartment projects with a focus on improving time performance. The methods employed include surveys and case studies, with data collected through the creation and distribution of questionnaires to experts, along with an analysis of results conducted by Company X. The findings indicate that the communication flow implemented at PT. X has proven to be valid and effective. However, several factors hinder the smooth communication flow, such as inadequate planning and scheduling of work, insufficient communication due to mismatched methods and technologies, inefficient information distribution systems, inadequate project budget planning, lack of resources, incomplete scheduling of time and resources, inappropriate listening and speaking skills, lack of empathy among parties, inadequate facilities and infrastructure, emotional conditions, and lack of mastery of communication techniques. Based on these findings, several actions are recommended to enhance communication flow, including improving planning and scheduling of work, using communication methods and technologies appropriate to field conditions, improving information distribution systems, ensuring project budget planning availability, increasing resources, creating comprehensive time and resource planning, enhancing listening and speaking skills, improving empathy among parties, upgrading facilities and infrastructure, controlling emotional conditions, and enhancing mastery of communication techniques. By implementing these recommendations, it is hoped that the communication flow in apartment projects can operate more effectively and efficiently, thereby improving overall project time performance.